Vitamins Modulate the Expression of Antioxidant Genes in Progesterone-Treated Pancreatic β Cells: Perspectives for Gestational Diabetes Management - Nathália Ruder Borçari; Jeniffer Farias dos Santos; Gustavo Roncoli Reigado; Bruna Letícia Freitas; Mariana da Silva Araújo; Viviane Abreu Nunes (International Journal of Endocrinology)
Gestational diabetes (GD) is a condition defined as carbohydrate intolerance and hyperglycemia beginning in the second trimester of pregnancy, which overlaps with the progesterone exponential increase. Progesterone has been shown to cause pancreatic β-cell death by a mechanism dependent on the generation of reactive oxygen species and oxidative stress. Herein, we studied the effect of this hormone on the expression of 84 genes related to oxidative stress and oxidant defense in pancreatic RINm5F cell lineage. Cells were incubated with 0.1, 1.0, or 100 μM progesterone for 6 or 24 h, in the presence or absence of the vitamins E and C. Among the investigated genes, five of them had their expression increased, at least 2-fold, in two different concentrations independently of the time of incubation, or at the same concentration at the different time points, including those that encode for stearoyl-CoA desaturase 1 (Scd1), dual oxidase 1 (Duox1), glutathione peroxidase 6 (GPx6), heme oxygenase 1 (Hmox1), and heat shock protein a1a (Hspa1a). Vitamins E and C were able to increase, in progesterone-treated cells, the expression of genes with antioxidant function such as Hmox1, but decreased Scd1 expression, a gene with prooxidant function. At cytoplasmic level, progesterone positively modulated Hmox1 and Hspa1a content. These results suggest that the protein encoded by these genes might protect cells against progesterone induced-oxidative damage, opening perspectives to elucidate the molecular mechanism involved in progesterone action in GD, as well as for the development of antioxidant strategies for the prevention and treatment of this disease.